How Twitter Works in Public Transportation: Case Study of Bus Rapid Transit in Jakarta and Semarang - Bokings, Surya Hidayat; Nurmandi, Achmad; Loilatu, Mohammad Jafar (Bina Nusantara University, 2020)
This research focuses on using social media (Twitter) as a medium for public transportation services (Bus Rapid Transit - BRT) in Semarang and Jakarta.This study uses Nvivo 12 Plus as a tool in qualitative research methods. The results of this study answer that the function regarding Twitter accounts of BRT in Semarang and Jakarta has several differences. The difference is based on information integration services, interaction information and transparency, and adaptive and responsive information services. In conclusion, the information integration on Twitter accounts of BRT in Semarang and Jakarta services works well, but a more dominant function is found in BRT in Jakarta. The Twitter account of BRT in Jakarta provides more information on transportation routes, such as the number of routes and fleets. BRT in Jakarta is a responsive account, responding to questions or mentions given by itsusers. The high level of activity makes the BRT Jakarta account more active. Moreover, the form of information conveyed by the Twitter account of BRT Semarang has its characteristics because it shows more the character of the region (Central Java)